EXPLORING THE PULVINAR PATH TO VISUAL CORTEX - Berman, Rebecca A. (2008)
The primary pathway for visual signals from the retina to cerebral cortex is through the lateral geniculate nucleus of the thalamus to primary visual cortex. A second visual pathway has been postulated to pass through the thalamic pulvinar nucleus and to project to multiple regions of visual cortex. We have explored this second visual pathway using a method that allows us to identify the inputs and outputs of pulvinar neurons. Specifically, we applied microstimulation in the superficial layers of superior colliculus (SC) to test for orthodromic activation of pulvinar neurons receiving input from SC. We also microstimulated the cortical motion area MT and tested for antidromic activation of pulvinar to identify neurons projecting to MT (and to determine the presence of orthodromic input back to pulvinar). In this initial report, we concentrate on two observations. First, we find that there are clusters of neurons in the pulvinar that receive input from SC along with neurons that project to MT or receive input from MT. Second, we find that neurons with input from SC have characteristics of the SC superficial layers: they respond to visual stimuli but do not discharge before saccadic eye movements. Neurons projecting to MT respond similarly to these SC-input neurons, while those receiving input from MT more frequently show directional selectivity as does MT. These findings indicate the visual nature of the signals conveyed in this pathway and shed light on the functional role of the thalamus in a possible second visual pathway.